Forest fire trend analysis and with factors efecting IT / Nor Fathiah Mohd Isa - Mohd Isa, Nor Fathiah (2020)
In Malaysia, forest fires have been a major cause of change in forest structure and also to change the natural functioning of ecosystems in the 20th century. In Kedah, it has recorded the highest number of fires caused by the El Nino phenomenon so far this year (Datuk Wira Wan Mohd Nor Ibrahim, 2016) and for that we only selected the area from Langkawi and Alor Setar in Kedah as it is the most affected area of forest fires supported by meteorological data. With this project, the goal is to analyze forest fire trends using hot spot analysis and their relationship with factors affecting them in Kedah using Geospatial information systems (GIS) and we use software such as ArcGis and QGis Software to analyze data from meteorologists and from the Department Fire Rescue. The objectives of this study were to identify the forest fire hot spots in the study area and to analyze the parameters selected for the forest fire areas that were the main focus of the study to determine the forest fire risk zone. In this study, the base map image was from (JUPEM) Department. From the base map hot spots, the results will come as a reference to analyze the area. Research data has been collected from 2014 to 2019. It looks at the differences each year when fires occur as well as finding and analyzing the selected factors based on data availability that cause fires. The results of this study were to establish hotspots for fire risk areas as a monitoring system to help the fire and rescue department (Fire) easily manage this area and to help them understand the reasons for the fire as a reference for them to prevent and help them to reduce the risk of fire in the area.